2014
DOI: 10.1177/2158244014528919
|View full text |Cite
|
Sign up to set email alerts
|

Moving Toward a Humanistic Social Studies and History Curricula

Abstract: Current reflective practices in the social studies are examined in light of how these strategies can add value and meaning to social studies curriculums. Many of these reflective practices were introduced within teacher education programs' social studies methods courses, to expose pre-service teachers to innovative teaching practices that could be used in the classroom. An ineffective textbook-centered curriculum has dominated education in the United States for over a century. The researchers in this article a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In this regard, Zevin (2013) mentioned that understanding the different roles you will play as a performing teacher for students in a social studies classroom will help you engage the majority of your students in a wide variety of learning activities. In addition, Berg and Shaw (2014) mentioned in their studies that there is a need for pedagogical models to revive the problematic social studies curriculum at school. Bauml (2016) should also force students to ask questions, evaluate and interpret resources, and think critically in order to endear social studies and improve students’ perspectives on social studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Zevin (2013) mentioned that understanding the different roles you will play as a performing teacher for students in a social studies classroom will help you engage the majority of your students in a wide variety of learning activities. In addition, Berg and Shaw (2014) mentioned in their studies that there is a need for pedagogical models to revive the problematic social studies curriculum at school. Bauml (2016) should also force students to ask questions, evaluate and interpret resources, and think critically in order to endear social studies and improve students’ perspectives on social studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on a reflective approach to teaching history and social studies curricula in the United States, Berg, and Shaw, [8] recommends new pedagogical models for reviving an ailing social studies program in the preschool system. Appropriate instructional strategies allow learners to give feedback and design challenging learning events that create connections and expansion of knowledge.…”
Section: Reflective Observation and Social Studiesmentioning
confidence: 99%
“…In a study on moving towards humanistic social studies and history curricula, Berg and Shaw [8] note that though teachers of SSC have acquired basic knowledge to convey to learners, the majority are not conversant with various learning styles developed to improve teaching and learning and are thereby, still constrained by conventional methods. As a consequence, Morris [9] indicated that learning suffers when a mismatch occurs between the style of the learner and the approach of the teacher.…”
Section: Introductionmentioning
confidence: 99%